Gerações em conflito nas narrativas de Etgar Kéret - Steinberg, Gabriel (Cadernos de Língua e Literatura Hebraica, 2019)
The sixth anthology of short narratives Takalá Biktzê hagalaksia (An incident in the far reaches of the Galaxy), won the Israeli writer Etgar Kéret the Sapir prize in 2018. As a mark of his writing, his narratives are addressed to the reader in a colloquial and informal language. His sometimes humorous writing has as characters common people who, in peculiar situations, have an extreme and even bizarre behavior.